Islamic Philanthropy and Social Welfare: Cash Waqf Policy Patterns as Social Funds for State Universities in Indonesia - Suryanto, Asep; Kusmayadi, Dedi; Rafiqi, Yusep; Nasrulloh, Agus Ahmad; Wijaya, Trisna (Journal of Posthumanism, 2025)
This article examines the policy patterns of cash waqf as a social fund in Indonesian state universities, analyzing its governance, sustainability, and developmental implications. Drawing on institutional economics and Islamic social finance, the study investigates how universities integrate waqf into higher education financing models. Data were derived from academic literature, policy documents, and recent studies on waqf sustainability and management innovations. The findings reveal that cash waqf is increasingly positioned as a strategic instrument to support scholarships, research, infrastructure, and community outreach. Universities adopt varying governance models, ranging from traditional trust-based structures to digital and professionally managed waqf schemes, reflecting institutional capacity and regulatory environments. Furthermore, the study identifies challenges in transparency, donor engagement, and alignment with national policies, yet emphasizes the potential of waqf to complement state funding and reduce educational inequality. By situating Indonesian practices within a comparative perspective, especially with Malaysia, Turkey, and Saudi Arabia, the research contributes to ongoing debates on sustainable higher education financing. The study highlights the dual role of waqf as both a faith-driven social obligation and an innovative tool for development, reinforcing its relevance in achieving educational and societal goals in Indonesia